2019
DOI: 10.3390/cells8080776
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin and Its Derivative Rifampicin Quinone Reduce Microglial Inflammatory Responses and Neurodegeneration Induced In Vitro by α-Synuclein Fibrillary Aggregates

Abstract: : Aggregated forms of the synaptic protein α-synuclein (αS) have been proposed to operate as a molecular trigger for microglial inflammatory processes and neurodegeneration in Parkinson´s disease. Here, we used brain microglial cell cultures activated by fibrillary forms of recombinant human αS to assess the anti-inflammatory and neuroprotective activities of the antibiotic rifampicin (Rif) and its autoxidation product rifampicin quinone (RifQ). Pretreatments with Rif and RifQ reduced the secretion of prototyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 63 publications
(83 reference statements)
2
47
0
1
Order By: Relevance
“…Candesartan cilexetil, an FDA-approved drug for treating cerebrovascular diseases, hypertension, and chronic heart failure, also able to inhibit the expression of TLR2 and TLR4 (Dasu et al, 2009), might reverse the pro-inflammatory phenotype of microglia activated by oligomeric α-syn (Daniele et al, 2015). Moreover, one recent study showed that the antibiotic rifampin and its autoxidation product rifampicin quinone prevented α-syn-induced TLR2- and P2X7-dependent microglial inflammatory responses in vitro (Acuna et al, 2019), which needs further investigation to confirm their potentials as anti-parkinsionian drugs. Interestingly, endurance exercise could exert neuroprotective effects in MPTP-induced PD mice by regulating the expression of TLR2 and its downstream signaling such as MyD88, TRAF6, and TAK1 (Jang et al, 2017; Koo et al, 2017).…”
Section: Potentials Of Microglia As a Therapeutic Target For Pdmentioning
confidence: 99%
“…Candesartan cilexetil, an FDA-approved drug for treating cerebrovascular diseases, hypertension, and chronic heart failure, also able to inhibit the expression of TLR2 and TLR4 (Dasu et al, 2009), might reverse the pro-inflammatory phenotype of microglia activated by oligomeric α-syn (Daniele et al, 2015). Moreover, one recent study showed that the antibiotic rifampin and its autoxidation product rifampicin quinone prevented α-syn-induced TLR2- and P2X7-dependent microglial inflammatory responses in vitro (Acuna et al, 2019), which needs further investigation to confirm their potentials as anti-parkinsionian drugs. Interestingly, endurance exercise could exert neuroprotective effects in MPTP-induced PD mice by regulating the expression of TLR2 and its downstream signaling such as MyD88, TRAF6, and TAK1 (Jang et al, 2017; Koo et al, 2017).…”
Section: Potentials Of Microglia As a Therapeutic Target For Pdmentioning
confidence: 99%
“…Rifampicin, another antibiotic known to exert multiple neuroprotective functions is suggested as potential treatment regime for PD [ 241 , 242 ]. Rifampicin and its derivative rifampicin quinone were found to reduce microglial inflammatory responses and neurodegeneration induced in vitro by α-Syn fibrillary aggregates [ 243 ]. Rifampicin might also reduce the cytotoxicity by promoting SUMOylation of α-Syn [ 244 ].…”
Section: Therapeutic Possibilities and Pharmaceutical Interventionmentioning
confidence: 99%
“…Pathological forms of α-synuclein, which are spread in the parenchymal tissue of the brain, can contribute to the disease process by stimulating inflammatory-type reactions through microglial cells (38). In one study, by using pure microglial cell culture, the inflammatory potential of three different forms of α-synuclein was tested and TNF-α and IL-6 release as inflammation markers were examined (39). As a result, a fibril form of α-synuclein was found to be the most inflammatory form of protein.…”
Section: Rifampicin α-Synuclein Aggregation and Sumoylation α-Synucmentioning
confidence: 99%
“…Rifampicin and its oxidized derivative, RifQ, have been shown to inhibit the activation of primary microglial cells induced by α-synuclein fibrils, which are inflammatory factors in PD (39,57). RifQ has been shown to have the potential to inhibit neurotoxic effects induced by microglial cells activated by α-synuclein fibrils.…”
Section: Rifampicin (Rif) and Its Oxidated Product (Rifq)mentioning
confidence: 99%